Efeito das toxinas purificadas pktx23c3, pktx28c4, pktx20c4, pntx19c1, pntx25a1, pntx37c2, pntx19c2, pntx3-2 na liberação de Glutamato emSinaptosomas Cérebro Corticais de Rato. - Daniel de Souza Carneiro (2010)
Studies revealed that the venom of the Brazilian armed spiderPhoneutria nigriventer contains potent neurotoxins that caused excitatory symptoms such as salivation, lachrymation, priapism, convulsions, flaccid and spastic paralysis. It was also reported that the main mechanism of action of those neurotoxins are effects on ion channels such as inhibition of the inactivation of Na+ channels, blockage of K+ channels and blockage of calcium channels. The venom from Phoneutria keyserlingi, as might be expected, contains a series of polypeptides that are very similar, but not identical, to the proteins previously obtained from the venom of P. nigriventer in terms of their amino acid sequences and biological activities. We evaluated the effects of some of the toxins ofP. nigriventer and P. keyserlingi on glutamate release and the decrease in [Ca2+]i by using synaptosomes of rat brain cortices and fluorimetric assays. Sequence comparisons between the Phoneutria toxins of both the species showed great similarity in the location of cysteine residues.However, thus far, no pharmacological assays were performed to evaluate the extension of those biochemical modifications. Our results showed that differences between the amino acid sequences of Phoneutria toxins of both the species lead to the significant changes in the pharmacological properties of these toxins